COMPARATIVE ANALYSIS OF TM5 FERTILIZER COSTS USING MANUAL AND Emdek Tractor METHOD IN DIVISION 4 OF KANDISTA REGIONAL SIAK PSM 5 PLANTATION PT. IVOMAS TUNGGAL - Alfonso; Febriana Roosmawati (RADJA PUBLIKA, 2026)
Fertilization is one of the maintenance activities that plays an important role in increasing the productivity of oil palm plants, but it is also the largest cost component in plantation management. The development of mechanization through the use of EMDEK tractors is expected to increase operational efficiency, so a study is needed regarding the cost comparison between manual and mechanical fertilization methods. This study aims to analyze the comparative costs of fertilizing mature plants (TM5) using manual methods and mechanical methods ( EMDEK tractors ) in Division IV of the Kandista PSM 5 Plantation of PT Ivomas Tunggal Regional Siak. The study was conducted from May–August 2026 using a comparative descriptive method. The research sample consisted of six blocks, namely three manual fertilization blocks and three mechanical fertilization blocks. Primary data were obtained through field observations and interviews, while secondary data were obtained from company administrative documents. Data analysis began with the Shapiro–Wilk normality test, then continued with an independent sample t-test at a significance level of 5%. The results of the study showed that the average cost of manual fertilization was Rp2,830,710 per hectare or Rp20,922 per tree , while the average cost of fertilization using an EMDEK tractor was Rp9,636,062 per hectare or Rp71,811 per tree . The largest cost component in the manual method was the cost of purchasing fertilizer, while in the EMDEK method it was dominated by the cost of TRC2 fuel. The results of the normality test showed that the data were normally distributed (p>0.05), thus fulfilling the assumptions for the t -test . The independent sample t-test produced a significance value of 0.004 (p<0.05), which indicated that there was a significant difference in fertilization costs between the manual method and the EMDEK tractor . Thus, the manual fertilization method had lower costs than the mechanical method at the research location.